Estimation of the zone of influence of Trbovlje power station on the basis of bioindication methods - Franc BATIČ; Natalija VIDERGAR-GORJUP; Helena ŠIRCELJ; Andreja BINELLI; Andrej STRNIŠA; Primož SIMONČIČ (Acta Agriculturae Slovenica)
Several bioindication methods were applied in order to determine the area of influence of emissions from the Trbovlje Thermal Power Plant. From 1991 to 1996 epiphytic lichens were mapped at 260 sites in the area from Vače to Veliko Širje and from Prebold to Jatna. Ten experimental plots, differing in distance from the thermal power plant and their air pollution level, were chosen for detailed analyses of Norway spruce (Picea abies (L.) Karst). Assessing damage to the number and density of branches and needles and analyses of macronutrients, chlorophyll a, chlorophyll b, a carotene, b carotene, zeaxanthin, lutein and ascorbic acid were chosen as markers of air pollution impact on Norway spruce. The conclusion was drawn that the emission area of the power plant exceeds the limits of the area researched. Pollution is somewhat lower in the north-west part of the investigated area. Dobovec, Kovk, Ostenk, Ravenska vas and Retje are strongly polluted. In 1991 and 1992 high concentrations of ozone were detected in Zasavje by monitoring with tobacco cultivars (Nicotiana tabacum L.). This was also confirmed by observing the response of cultivars of white clover, beans, sunflower and selected natural species at Kovk. The mapping of lichens and the analysis of biochemical parameters of spruce needles proved to be a highly useful bioindication method.